2020
DOI: 10.1002/lary.28652
|View full text |Cite
|
Sign up to set email alerts
|

Rural–Urban Disparities in Otolaryngology: The State of Illinois

Abstract: Objectives/Hypothesis To highlight rural–urban disparities in otolaryngology, and to quantify the disparities in access to otolaryngology specialist care across Illinois. Several studies across disciplines have shown increased prevalence and severity of disease in rural communities, relative to their urban counterparts. There is very little published quantifying a disparity in rural access to otolaryngologists. Study Design Population study. Methods Counties in Illinois were classified based on urbanization le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“… 26 Finally, large-scale practices, in a world with increased consolidation, may trend toward urbanization and ultimately widen health care disparities by limiting access to care in rural areas. 12 , 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 Finally, large-scale practices, in a world with increased consolidation, may trend toward urbanization and ultimately widen health care disparities by limiting access to care in rural areas. 12 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…26 Finally, large-scale practices, in a world with increased consolidation, may trend toward urbanization and ultimately widen health care disparities by limiting access to care in rural areas. 12,27 Given these concerns, further research is necessary to assess the influence of practice consolidation on health care costs, access, and quality of care in the field of otolaryngology. A continued trend toward large-scale practice consolidation could lead to the demise of the solo provider practice in otolaryngology, and given the potential implications on the delivery of quality health care services, the American Academy of Otolaryngology-Head and Neck Surgery and other national specialty societies should monitor these trends closely.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research among otolaryngology‐head and neck surgery patients has shown varying levels of online health (eHealth) literacy, with lower levels among rural populations 27 . Since rural populations have worse health outcomes, decreased access to care, and longer travel times, 28‐30 telehealth could help address many of these sources of disparities. However, interventions to overcome technical issues will be required to improve telehealth availability, education, and utilization among rural patients.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern may be partially attributable to increased specialization and a higher likelihood of academic affiliation among urban ORLs, a more comprehensive practice among rural providers, as well as a higher density of Medicaid/ Medicare patients in rural areas. 41 Given the significantly higher prevalence of female ORLs practicing in urban areas (93.1%), there is a large difference in sample size between the geographic cohorts. In a comparison of regional trends, female ORLs in the Northeast accrued significantly more total Medicare payments and saw a higher number of unique Medicare patients than those practicing outside the Northeast, likely signaling differences in regional reimbursement rates, practice models, and Medicare population density.…”
Section: Discussionmentioning
confidence: 99%